Emptying slag ladle on No. 2 experimental blast furnace (1932)
General view of a worker emptying the slag ladle on the No. 2 experimental blast furnace on a burden (a load, especially a heavy one) of phosphate at the U.S. Department of Agriculture's Fixed Nitrogen Research Laboratory located in Washington, D.C. Per a notation accompanying the photograph, the two individuals visible in the photograph are identified as follows (in no particular order): Reed and Hill. The Fixed Nitrogen Research Laboratory (F.N.R.L.) was established at American University in 1919 under the directorship of Arthur B. Lamb. Initially part of the War Department, the F.N.R.L. was the successor to several wartime initiatives to develop a secure domestic supply of nitrate compounds necessary for the manufacture of explosives during World War I. With a staff of about 110 individuals, including 35 to 50 chemists, the F.N.R.L. focused on the manufacture, production, and development of products of atmospheric nitrogen, including munitions and fertilizers.
Keywords: Nitrogen fertilizer industry; Blast furnaces; United States. Bureau of Chemistry and Soils; Slag; Phosphatic slag; Slag as fertilizer; Furnaces; United States. Department of Agriculture